Association of arthrogryposis in neonates with microcephaly due to Zika virus - a case serie - Alvino,Ana Catarina Matos Ishigami (2016)
Abstract Introduction: in 2015 an increasing number of congenital microcephaly cases were associated to maternal infection due to Zika virus. Some of these patients presented other alterations and arthrogryposis was the most frequently found. Arthrogryposis is defined as congenital joint contractures involving at least two different areas of the body. Description: arthrogryposis was found in 18 patients with congenital microcephaly due to Zika virus. 67% of the cases were vaginal deliveries. 50% of resuscitation performed in the delivery room was necessary. The mean birth weight was 2.371g, gestational age was 39 weeks and the head circumference was 28.3cm, 15 (83%) of these patients presented severe microcephaly. All the neonates resulted in concomitant hip joints and some also had knees, ankles and wrists affected. Nine neonates (50%) presented an early respiratory distress and four (22%) died due to respiratory failure. Discussion: the neurological result found in patients with Congenital Zika Syndrome seems to be associated to the maternal infection period. During the early stages of embryogenesis, in addition to microcephaly, could be related to the peripheral motor nerves leading to fetal akinesia, joint stiffness and arthrogryposis. These neonates tend to present greater morbimortality with the worst prognosis.